The Influence of Bank Characteristics on Financial Performance with Intellectual Capital as Intervening Variable (Study on National Commercial Banks in Indonesia) - Neneng Susanti; Muhammad Bayu Aji Sumantri; Tanti Irawati Mukhhlis; Vincentia Wahju Widajatun (Universitas Negeri Makassar, 2022)
This study aims to examine the effect of bank characteristics on financial performance using 7 financial proxies on bank characteristics from market concentration of third party funds (HDPK), credit market concentration (HLOA), capital adequacy (CAR), bank liquidity (LDR), bank efficiency. (BOPO), non-performing loans (NPL), leverage (LEV), and Financial Performance with the proxy of Return On Assets (ROA) as the dependent variable and Intellectual Capital as the Intervening variable. The method of data collection in this study is to collect secondary data. This research is focused on National Commercial Banks in Indonesia. The results of this study obtained that there is a significant effect between Bank Characteristics on Financial Performance with a T-Statistic of (5.360 > 1.96) and a coefficient value of 0.838. The effect of bank characteristics on intellectual capital has a significant effect with a T-statistic of (4,089 > 1.96) and a coefficient value of 0.626. Furthermore, the influence of Intellectual Capital on Financial Performance does not have a significant T-statistical effect of (0.304 < 1.96) and the coefficient value is -0.058.